2011
DOI: 10.1080/19320248.2011.549801
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to EBT Use at Farmers' Markets: Lessons in Empowerment Evaluation from Rural Ohio

Abstract: Increasing attention and funding are being directed toward enabling low-income individuals to use federal food assistance at farmers' markets. Empowerment evaluation was conducted of the Oxford Farmers Market Uptown's electronic benefit transfer (EBT)program to identify and address barriers preventing individuals from using EBT as payment for locally produced goods. The evaluation revealed that shopping for goods at the farmers' market could be affordable and culturally appropriate but that lack of knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
4
12
0
Order By: Relevance
“…Findings support data from other studies that suggest low-income consumers’ have limited knowledge about FMs, 24 and when informed, use may be deterred by perceptions of cost, 24 inconvenience, 10,25 and safety concerns. 8,10 This data underscores the need to consider lack of awareness, misperceptions, attitudes, and shopping behaviors when designing interventions to improve access by this target population.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Findings support data from other studies that suggest low-income consumers’ have limited knowledge about FMs, 24 and when informed, use may be deterred by perceptions of cost, 24 inconvenience, 10,25 and safety concerns. 8,10 This data underscores the need to consider lack of awareness, misperceptions, attitudes, and shopping behaviors when designing interventions to improve access by this target population.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with identified barriers to EBT use at FMs in rural communities. 24 Furthermore, FM placement away from supermarkets and limited operating hours prevent opportunities for convenient access during normal grocery trips (i.e., perceived inaccessibility and poor accommodation), which supports other findings that FMs are used less often by convenience-oriented consumers. 10,25 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Notably, study participants who never shopped at a FM or had not shopped at one in the past year were significantly less likely to know they had a FM near their home even though all participants lived within 1 mile of a FM. This finding corroborates other research that found coordinated marketing and outreach efforts to be lacking in many FM implementation models (Colasanti, Conner, & Smalley, ; Flamm, ; Leone et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Many SNAP participants are unaware that SNAP benefits are accepted at farmers markets throughout the country (Flamm, 2011;Wetherill & Gray, 2015). As a result, only 0.01% of SNAP benefits are being redeemed at farmers markets each year (Dimitri, Oberholtzer, & Nischan, 2013).…”
Section: Resultsmentioning
confidence: 99%